Correlation of Doppler assessment of fetal aortic isthmus with perinatal outcome in intrauterine growth restriction - Tantuway, Bhoomika; Mala, Y. M.; Garg, Anju; Tripathi, Reva (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The objective of the present study was to find out association between aortic isthmus Doppler changes and perinatal outcome in growth restricted fetuses with placental insufficiency. Methods: It is a prospective case control study, cases were 43 pregnant women with fetal growth restriction (FGR) with abnormal umbilical artery (UA) Doppler while 43 pregnant women with FGR but normal UA doppler, matched with period of gestation were taken as control. The direction of blood flow in aortic isthmus studied which may be antegrade, absent or retrograde and correlation between qualitative parameters of umbilical artery, aortic isthmus and ductus venosus were studied. Quantitative parameters, PI and RI were also calculated. Patients were managed as per hospital protocols. Perinatal outcome and any adverse event e.g. stillbirth, neonatal death, respiratory distress syndrome, intensive care unit stay >14 days etc. was noted. Results: The number of intrauterine death (IUD) and still birth was increased in women with absent and retrograde flow in aortic isthmus, 66.7% and 71.4% respectively (p value <0.001). Retrograde blood flow in the aortic isthmus is consistently associated with absent or reverse end diastolic velocity in umbilical artery and ductus venosus. Conclusions: Doppler of aortic isthmus is an additional parameter to assess severity of FGR. It plays an important role in termination of preterm FGR fetuses.